A Comparative Analysis of Gamified Educational Applications For Enhancing Classroom Engagement - Nur Azwa Humaira Mohd Norazizi; Muhammad Haziq Rahman Shafawi; Siti Munirah Mohd; Nurhidaya Mohamad Jan; Shafinah Kamarudin; Fadzidah Mohd Idris; Ts. Dr. Hatika Kaco; Amelia Natasya Abdul Wahab; Nur Shamim Hamzah; Engku Nor Hamidah Engku Abdul Rahman (Academic Inspired Network, 2025)
Indexed Publication (Tier 3)